Descriptive Analysis of Adaptive Behavior in Phelan–McDermid Syndrome and Autism Spectrum Disorder - Serrada-Tejeda, Sergio; Martínez-Piédrola, Rosa M.; Máximo-Bocanegra, Nuria; Sánchez-Herrera-Baeza, Patricia; Pérez-de-Heredia-Torres, Marta (Frontiers in Neuroscience, 2022)
The variety in symptomatology and clinical presentation of individuals diagnosed with Phelan-McDermid Syndrome (PMS) can delay medical diagnosis, so identifying specific neurobehavioral variables and facilitating differential diagnosis with patients with idiopathic Autism Spectrum Disorder (ASD) can guide early detection. Methods: A descriptive analysis of the level of adaptive behavior in 50 patients diagnosed with PMS was performed (SHANK3deletion: N=44; SHANKmutation: N=6). Subsequently, a comparative analysis was performed with 28 children aged between 4 years and 6 years and 11 months (SHANK3deletion =14; ASD=14). Differences between the two groups were evaluated and Bonferroni correction was applied for multiple comparisons. Results: Differences were identified in the variables of communication (z=-2.715, p=0.007), Self-Direction (z=-2.199, p=0.028) and social participation (z=-3.190, p=0.001), with better adaptive behavior skills being observed in participants with a SHANK3mutation. Better adaptive skills in the sample of participants with ASD, were found and statistically significant differences were identified in the variables of academic skills (z=-3.084, p=0.002), use of community resources (z=-1.889, p=0.050) and health and safety (z=-2.90, p=0.004). Conclusions: participants with SHANK3mutation show better communication and social participation skills than those with a diagnosis of SHANK3deletion. The observed differences between ASD and individuals with PMS reflect deficits in practical and conceptual adaptive skills that may limit and hinder daily adaptive functioning.